Teachers’ Beliefs and Practice on Meaning-Making in the Teaching of Literature - Moning, Norherani (2007)
The main purpose of the study was to examine teachers’ beliefs and practice regarding meaning-making in the teaching of literature. The study was carried out through a detailed investigation of two research questions: (1) what are teachers’ beliefs regarding meaning-making in the teaching of literary texts? (2) How do teachers make meaning accessible to students in a literature classroom? These questions were continuously addressed throughout the study with the specific concern of investigating teachers’ beliefs in meaning-making, understanding the process of meaning-making in the teaching of literature and linking these concepts to actual classroom practice in the English language teaching classroom in the secondary schools in Malaysia. A naturalistic qualitative inquiry was selected as the methodology of the study since it was deemed the most appropriate for a phenomenon of this nature. Data was gathered and generated from eight teachers from two government schools. The participants were selected based on criterion reference purposive sampling. The data collection method to achieve the purpose of this study was in-depth interview, non-participant lesson observation and document review. Each interview lasted one to two hours, were recorded using digital audio recorder, transcribed verbatim, and analysed manually. In addition, a non-participant lesson observation of teachers’ teaching the literature component was made available to the researcher by some of the participants. Documents in the form of teachers’ lesson plans, syllabus and students’ products were also analysed. The trustworthiness of the study was ensured through member checks, peer examination, triangulation of data source and audit trail. The findings yielded nine beliefs regarding meaning making and three approaches employed by the participants in the literature classroom. The findings were further conceptualised to form a thematic portrayal of teachers’ beliefs and practice. The study concludes by constructing a model of teachers’ beliefs and practice in meaning-making which could enhance understanding of the phenomenon of meaning-making process in relation to teachers’ beliefs and practice. Implications of the study focus on training of pre-service and in-service Teacher Education. Recommendations for further research were also suggested.